Investigation of Antioxidant, Hypoglycemic and Anti-Obesity Effects of Euphorbia Resinifera L. - Kaoutar Benrahou; Otman El Guourrami; Hanae Naceiri Mrabti; Yahia Cherrah; My El Abbes Faouzi (Korean Pharmacopuncture Institute, 2022)
Objectives: The aim of this work is to evaluate the in vitro antioxidant, hypoglycemic, and antiobesity effects of Euphorbia resinifera extracts and investigate the phenolic constituents and the toxicity of these extracts.Methods : Phytochemical screening was performed to detect polyphenols and flavonoids. Antioxidant activity was evaluated by four methods (DPPH, ABTS, H2O2, and xanthine oxidase inhibition). The hypoglycemic effect was determined by the inhibition of α-amylase and α-glucosidase enzymes in vitro and via a starch tolerance study in normal rats. The antiobesity effect was estimated by in vitro inhibition of lipase.Results : Phytochemical screening revealed that the ethanolic extract was rich in polyphenols (99 ± 0.56 mg GEA/g extract) and tannins (55.22 ± 0.17 mg RE/g extract). Moreover, this extract showed higher antioxidant activity in different tests: the DPPH assay (IC50 = 53.81 ± 1.83 μg/mL), ABTS assay (111.4 ± 2.64 mg TE/g extract), H2O2 (IC50 = 98.15 ± 0.68 μg/mL), and xanthine oxidase (IC50 = 10.26 ± 0.6 μg/mL). With respect to hypoglycemic effect, the aqueous and ethanolic extracts showed IC50 values of 119.7 ± 2.15 μg/mL and 102 ± 3.63 μg/mL for α-amylase and 121.4 ± 1.88 and 56.6 ± 1.12 μg/mL for α-glucosidase, respectively, and the extracts lowered blood glucose levels in normal starch-loaded rats. Additionally, lipase inhibition was observed with aqueous (IC50 = 25.3 ± 1.53 μg/mL) and ethanolic (IC50 = 13.7 ± 3.03 μg/mL) extracts.Conclusion : These findings show the antioxidant, hypoglycemic, and hyperlipidemic effects of E. resinifera extracts, which should be investigated further to validate their medicinal uses and their pharmaceutical applications.